2023
DOI: 10.1073/pnas.2307604120
|View full text |Cite
|
Sign up to set email alerts
|

Structural polymorphisms within a common powdery mildew effector scaffold as a driver of coevolution with cereal immune receptors

Abstract: In plants, host–pathogen coevolution often manifests in reciprocal, adaptive genetic changes through variations in host nucleotide-binding leucine-rich repeat immune receptors (NLRs) and virulence-promoting pathogen effectors. In grass powdery mildew (PM) fungi, an extreme expansion of a RNase-like effector family, termed RALPH, dominates the effector repertoire, with some members recognized as avirulence (AVR) effectors by cereal NLR receptors. We report the structures of the sequence-unrelated barley PM effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 71 publications
3
22
0
Order By: Relevance
“…These findings highlighted that AF2 predicts MAX effector structures in a highly reliable and precise manner even at relatively low pLDDT scores. Similar observations were made in other recent studies where experimentally resolved structures of fungal effectors were compared with AF2 predictions, as for example in the case of LARS [43], FOLD [44] and RALPH [45] effectors. Comparison with a published study testing ab initio approaches using Rosetta or the two web servers Robetta and QUARK to model MAX effectors with already known structures [46] confirmed that AF2 outcompetes other strategies for the prediction of MAX effector structures.…”
Section: Discussionsupporting
confidence: 84%
“…These findings highlighted that AF2 predicts MAX effector structures in a highly reliable and precise manner even at relatively low pLDDT scores. Similar observations were made in other recent studies where experimentally resolved structures of fungal effectors were compared with AF2 predictions, as for example in the case of LARS [43], FOLD [44] and RALPH [45] effectors. Comparison with a published study testing ab initio approaches using Rosetta or the two web servers Robetta and QUARK to model MAX effectors with already known structures [46] confirmed that AF2 outcompetes other strategies for the prediction of MAX effector structures.…”
Section: Discussionsupporting
confidence: 84%
“…AVRA1 and BEC1016 both interact with HvERdj3B and both enter the ER posttranslationally and signal peptide-independently. They have very diverse amino acid sequences, but appear derived from an ancient RNAse and may potentially be structurally related (Cao et al, 2023;Pedersen et al, 2012), which may explain their shared functions. Interestingly, the ERQC machinery is known to engage in the post-translational ER protein uptake through the Sec61 translocon complex (Hassdenteufel et al, 2019;Zimmermann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CSEP0008 (gene ID BLGH_03023) is recognized by MLA1, and thus named AVRA1 (Lu et al, 2016). Other recognized CSEPs are CSEP0059 (AVRA7), CSEP0174 (AVRA9), CSEP0141 (AVRA10 and AVRA22), and CSEP0372 (AVRA13) (Bauer et al, 2021;Cao et al, 2023;Lu et al, 2016;Saur et al, 2019;). AVRA6 is represented by three near-identical copies in the DH14 genome, BLGH_00709 (CSEP0254), BLGH_00708 and BLGH_07091 (Bauer et al, 2021;Cao et al, 2023), which may be expressed in an isolate-specific manor (Velásquez-Zapata et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, CSEP0008 (gene ID BLGH_03023) is recognized by MLA1, and thus named AVR A1 (Lu et al., 2016 ). Other recognized CSEPs are CSEP0059 (AVR A7 ), CSEP0174 (AVR A9 ), CSEP0141 (AVR A10 and AVR A22 ), and CSEP0372 (AVR A13 ) (Bauer et al., 2021 ; Cao et al., 2023 ; Lu et al., 2016 ; Saur et al., 2019 ). AVR A6 is represented by three near‐identical copies in the DH14 genome, BLGH_00709 ( CSEP0254 ), BLGH_00708 and BLGH_07091 (Bauer et al., 2021 ; Cao et al., 2023 ), which may be expressed in an isolate‐specific manner (Velásquez‐Zapata, Smith, et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%